2020
DOI: 10.1108/jeee-03-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring challenges and opportunities of the new social entrepreneurs: the case of indigenous musicpreneurs in KP Pakistan

Abstract: Purpose The purpose of this paper is to examine the struggle of and explore opportunity structure for a special class of social entrepreneurs, known as musicpreneurs, in the context of a war-ridden conflict region of Pakistan. A unique case of Pashtun musicians is undertaken, who are confronted with multiple challenges and barriers while commercializing their musical skills. It provides a holistic account of a journey towards self-sustenance from the perspective of real-life musicpreneurs living in harsh socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…One of the developing nations such as Pakistan has been facing daunting socio-economic challenges particularly in the areas of education, food and health-care (Iqbal et al , 2018). Apart from these inefficiencies the climatic changes, natural disasters and war on terror have accelerated to worsen the overall socio-economic environment of the country (Muhammad et al , 2020). During Global Entrepreneurship Summit held in Istanbul, Turkey, Priya Shah suggested that in Pakistan Social Entrepreneurship can address these day to day increasing challenges faced by government, private sector, NGOs, academia and young people by offering the right aspirations and building homegrown solutions to these socio-economic ailments in the country (Khan and Avinash, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the developing nations such as Pakistan has been facing daunting socio-economic challenges particularly in the areas of education, food and health-care (Iqbal et al , 2018). Apart from these inefficiencies the climatic changes, natural disasters and war on terror have accelerated to worsen the overall socio-economic environment of the country (Muhammad et al , 2020). During Global Entrepreneurship Summit held in Istanbul, Turkey, Priya Shah suggested that in Pakistan Social Entrepreneurship can address these day to day increasing challenges faced by government, private sector, NGOs, academia and young people by offering the right aspirations and building homegrown solutions to these socio-economic ailments in the country (Khan and Avinash, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals shunned by society, who live under unfavorable conditions and are unable to pursue traditional careers, turn to entrepreneurship as alternative means of social insertion and mobility (Vale, 2014; Muhammad et al , 2021). The statements made by representatives of waste pickers’ cooperatives and associations indicate the discrimination they are subjected to, as well as their difficulty in pursuing traditional careers, as highlighted by Representative 5: ‘then, when someone seeks a cooperative, it happens because he/she is already subjected to discrimination out there.” According to Miller and Breton-Miller (2017), individuals belonging to this social class go through processes, and present features, different from those of entrepreneurs from other social classes.…”
Section: Discussionmentioning
confidence: 99%
“…The statement by Representative 4 reveals the sense of the relevant role played by activities developed by these recyclers' cooperatives in protecting the environment, as well as the economic and social development (Paltasingh, 2012) enabled by the entrepreneurial traits of representatives of these cooperatives and associations. In other words, they are micro-level entrepreneurs, who are often marginalized by society, but who are aware that they can contribute to their community (Muhammad et al, 2021). Setting goals to drive work practices is one of the features of entrepreneurial behavior.…”
Section: Challenges Posed By the Poverty Contextmentioning
confidence: 99%
“…As reciprocity can contribute to developing or improving an entrepreneurial ecosystem, generating employment and income, policymakers should encourage such a condition. Further, reciprocity may be essential for some types of entrepreneurship, such as social or those developed by immigrants and other minority groups, more common in emerging and developing contexts (Khaw et al , 2021; Muhammad et al , 2021). For instance, studies have shown that most women in most countries also have appropriate reciprocity as the mainstay of their business initiatives.…”
Section: Discussionmentioning
confidence: 99%